The design of a recording traction dynamometer - Faris, Smith; Ramsey, Lester Allen (My University, 1906)
Introduction: Dynamometers are instruments used for measuring power and are divided into three classes: (1) brake or absorption dynamometers, in which the power of a rotating shaft or wheel is absorbed or converted into heat by the fraction of a brake; (2) transmission dynamometers, in which the power of a rotating shaft is measured during its transmission through a belt or other connection to another shaft, without being absorbed; and (3) traction dynamometers which are used for determining the power required to pull a car, wagon or other load. It is one of the latter class, especially adapted to traction engines, with which this thesis deals. We based our calculations regarding the tractive capacity necessary on data taken in 1905 by Messrs. Barnard, Carnahan and Thompson on the tractive power of a twenty two horse power traction engine, in which the greatest pull was 4000 pounds. We thought best to allow for a greater pull than this and so decided that our dynamometer should have a tractive capacity of 5000 pounds.
Citation: Faris, Smith and Ramsey, Lester Allen. The design of a recording traction dynamometer. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Dynamometers; Specifications; Schematic Diagrams; Theses; Manuscripts (documents)